2016
DOI: 10.1080/10410236.2016.1146567
|View full text |Cite
|
Sign up to set email alerts
|

NekNominate: Social Norms, Social Media, and Binge Drinking

Abstract: This study examines the social-media-based binge drinking game NekNominate and how this phenomenon is related to social norms. NekNominate is a game wherein players are nominated to film themselves "neking" or chugging copious amounts of alcohol or drinking alcohol in a novel or humorous manner. The player then nominates other players via social media who then have a specific timeframe in which they must complete their challenge or face ridicule. Health communication research on drinking behaviors has often lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Half of all beverages depicted on celebrity social media accounts were alcoholic beverages, as were nearly two-thirds (63.4%) of beverages in sponsored posts. This finding is consistent with research on the ease with which youths can access alcohol content on social media 16 , 17 , 18 , 26 , 28 and with the finding that social media posts frequently associate alcohol with positive attributes. 28 Depicting alcohol as such a large share of beverages matters because social media exposure to alcohol content is associated with alcohol consumption in adolescents and young adults, 17 , 58 and these processes are mediated, in part, by perceived norms.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Half of all beverages depicted on celebrity social media accounts were alcoholic beverages, as were nearly two-thirds (63.4%) of beverages in sponsored posts. This finding is consistent with research on the ease with which youths can access alcohol content on social media 16 , 17 , 18 , 26 , 28 and with the finding that social media posts frequently associate alcohol with positive attributes. 28 Depicting alcohol as such a large share of beverages matters because social media exposure to alcohol content is associated with alcohol consumption in adolescents and young adults, 17 , 58 and these processes are mediated, in part, by perceived norms.…”
Section: Discussionsupporting
confidence: 89%
“…28 Depicting alcohol as such a large share of beverages matters because social media exposure to alcohol content is associated with alcohol consumption in adolescents and young adults, 17,58 and these processes are mediated, in part, by perceived norms. [16][17][18] Although beverage nutrition scores were not associated with likes and comments, trends by celebrity demographics suggested that beverage posts by male celebrities depicted higher alcohol content than did beverage posts by female celebrities. In addition, beverage posts by music artists depicted higher sugar content than did beverage posts from athletes or from actors, actresses, and television personalities.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…NekNominate seems to be an on-off phenomenon related to 2013-2014; nevertheless, Wombacher et al [ 23 ] wrote about it and its relation to social norms in June 2016. Although NekNomination is no longer shown in the media and is now not a search trend in Google or Twitter, this does not mean the practice has disappeared: modern video exchange methods, (eg, Snapchat or WhatsApp) are now more private than in the past and allow users to exchange videos between individuals or groups of selected friends.…”
Section: Discussionmentioning
confidence: 99%
“…NekNominate provides a high-profile example which shows that user-created alcohol promotion can also appear across multiple channels. NekNominate was an online drinking game in which an individual posted a video of themselves consuming an alcoholic drink before nominating a peer, by tagging them on social media, to continue the practice within the next 24 hours (Wombacher, Reno, & Veil, 2016;Zonfrillo & Osterhoudt, 2014). The game not only generated content from users, but also produced public fan pages (Neknominate, n.d.) and video compilations of individuals taking part (Viral Videos Today, 2014).…”
Section: User-created Alcohol Promotion: Definition Assumptions Andmentioning
confidence: 99%